Potential crosstalk of the interleukin‐6–heme oxygenase‐1‐dependent mechanism involved in resistance to lenalidomide in multiple myeloma cells. (14th January 2016) - Wu, Weibing; Ma, Dan; Wang, Ping; Cao, Lu; Lu, Tangsheng; Fang, Qin; Zhao, Jiangyuan; Wang, Jishi
Abstract : Interleukin (IL)‐6 is one of the most important survival factors in multiple myeloma (MM), and determines the poor prognosis of MM. IL‐6 mainly has a paracrine bone marrow stromal cell origin and an autocrine MM cell origin. As an enzyme having cytoprotective effects, heme oxygenase‐1 (HO‐1) promotes the growth and drug resistance of various malignant tumors. HO‐1 expression levels in bone marrow CD138 + cells of MM patients were significantly higher than those in healthy donors, and positively correlated with both serum IL‐6 and intracellular IL‐6 mRNA expression levels. Culture of U266, RPMI8226 and CD138 + cells with exogenous IL‐6 in vitro induced high HO‐1 expression levels and allowed them to resist lenalidomide. It is hypothesized that this was probably attributable to IL‐6‐mediated activation of the Janus kinase 2–signal transducer and activator of transcription 3 pathway. In contrast, without IL‐6 coculture, enhanced HO‐1 expression in U266, RPMI8226 and bone marrow CD138 + cells from MM patients significantly inreased IL‐6 mRNA expression levels and facilitated autocrine IL‐6 production. The findings were associated with high HO‐1 expression‐enhanced p38 mitogen‐activated protein kinase phosphorylation. Reduced HO‐1 expression sensitized MM cells to lenalidomide. Therefore, we postulated that IL‐6 in the bone marrow microenvironment of MM patients stimulated high HO‐1 expression in MM cells and their resistance to lenalidomide. High HO‐1 expression also stimulated autocrine IL‐6 production, and exacerbated drug resistance and disease. This study supports the use of HO‐1 as a possible marker for both MM prognosis and drug resistance, and as a potential therapeutic target. Abstract : IL‐6 in the bone marrow microenvironment stimulates high HO‐1 expression in MM cells and high HO‐1 expression also promotes autocrine IL‐6 production, supporting an autocrine proliferative loop.